Cyclin G2 upregulation impairs migration, invasion, and network formation through RNF123/Dvl2/JNK signaling in the trophoblast cell line HTR8/SVneo, a possible role in preeclampsia. Issue 2 (17th November 2020) - Sun, Manni; Gao, Jinlan; Meng, Tao; Liu, Shenghuan; Chen, Haiying; Liu, Qi; Xing, Xuesha; Zhao, Chenyang; Luo, Yang
Abstract: Disruption of extravillous trophoblast (EVT) migration and invasion is considered to be responsible for pathological placentation in preeclampsia (PE). Cyclin G2 (CCNG2) is an atypical cyclin that inhibits cell cycle progression. However, its biological function and underlying molecular mechanism in PE are poorly understood. In this study, clinical data demonstrated that CCNG2 was significantly upregulated in PE placenta and associated with invasive EVT dysfunction. Additionally, Ccng2 knockout led to an attenuation of PE‐like symptoms in the PE mouse model produced via treatment with NG‐nitro‐L‐arginine methyl ester (L‐NAME). In vitro, CCNG2 inhibited the migration, invasion, and endothelial‐like network formation of human trophoblast cell line HTR8/SVneo. Mechanically, CCNG2 suppressed JNK‐dependent Wnt/PCP signaling and its downstream indicators including epithelial‐to‐mesenchymal transition (EMT) markers and matrix metalloproteinases (MMPs) via promoting the polyubiquitination degradation of dishevelled 2 (Dvl2) protein in HTR8/SVneo cells. We also discovered that the E3 ligase Ring finger protein 123 (RNF123), as a novel CCNG2 target among HTR8/SVneo cells, interacted with Dvl2 and participated in CCNG2‐induced polyubiquitination degradation of Dvl2. Moreover, we verified that the treatment of HTR8/SVneo cells with RNF123‐specific siRNA improved polyubiquitination‐induced degradation of Dvl2 and the activity of Wnt/PCP‐JNK signaling mediated by CCNG2. Taken together, our results reveal that the CCNG2/RNF123/Dvl2/JNK axis may be involved in the pathogenesis and progression of PE through trophoblastic cell function modulation, thus probably providing us with new therapeutic strategies for PE treatment.